ARCHAEAL AND BACTERIAL LIPIDS IN AUTHIGENIC CARBONATE CRUSTS FROM EASTERN MEDITERRANEAN MUD VOLCANOES - Bouloubassi I.; Aloisi G.; Pierre C.; Pancost R.D.; Hopmans E.; Damsté J.S.S. (My University, 2006)
We investigated the distributions and δ13C values of lipid biomarkers in authigenic methane-related carbonate crusts formed on eastern Mediterranean mud volcanoes. A highly diverse suite of microbial membrane lipids was detected. Strongly 13C-depleted lipids diagnostic for archaea include isoprenoid glycerol diethers, isoprenoid glycerol dialkyl glycerol tetraethers and several C20-C35 isoprenoid hydrocarbons. Bacterial lipids mainly consist of dialkyl glycerol diethers, branched fatty acids and hopanoids, showing important 13C-depletions, albeit less than archaeal lipids. The data provide further evidence for the involvement of archaea and bacteria in the anaerobic oxidation of methane (AOM) and in the sequestration of methane-derivedarying distributionortia, expanding on existing work at cold seeps. Distinctive biomarker features - and inferred microbial assemblages - are observed in these crusts, in agreement with available phylogenetic data for the samples. Our results support the potential of lipids for distinguishing methanotrophic communities. Despite the observed variances, conservative features in the abundances and isotopic offsets of microbial biomarkers occur, likely reflecting the overall relationships between archaea and bacteria and the nature of carbon flow between them. © 2005 Elsevier Ltd. All rights reserved.